ANALISIS WANPRESTASI KEAGENAN PENJUALAN KENDARAAN BERMOTOR (Studi CV Nobel Perdana Kabupaten Tulang Bawang) - Heri Yulianto (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
Standard by PT Sumber Trada Motor leads to no availability of vehicles to be sold by outlets CV Nobel Perdana. Giving great discounts and gifts, making consumers tend to buy directly from outlets PT Sumber Trada Motor. This agency system turns into competition due to the sales and market share CV Nobel Perdana excellent. The usefulness of this study as a researcher competence in the field of business law violations agreement. The problem of research is how the legal provisions breach agreement, the implementation of competition law to businesses which violate the agreement. Is expected to the Government through the KPPU to crack down on employers who violate the law No. 5 of 1999 on Competition, so as to control the businesses that destroy the independence of other businesses. Keywords: Standard, Agreement, Agency